2023
DOI: 10.24875/bmhime.m18000030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plaque and dental decay in the first permanent molar in a school population of south Mexico City

Abstract: Background:The first permanent molar is susceptible to acquire tooth decay since its eruption due to its anatomy and because it has been exposed before the other teeth. Methods: An observational, prolective, transversal, and comparative study in 194 students, with a mean age of 9.9 ± 1.8 years. The evaluation of the dentobacterial plaque (DBP) was analyzed using the O'Leary index and the tooth decay experience with the DMFS (sum of decayed, missing, extracted and filling dental surfaces) and DMFT (sum of decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
1
1
Order By: Relevance
“…The mean DMFT in present study was found to be 0.96, a finding similar to the study by Chirca EM et al 13 who reported mean DMFT as 0.7. Studies done by Desai V et al 14 Taboada AO et al 15 and Sadeghi M 16 reported mean DMFT to be 0.12, 1.4 and 1.9 respectively, which is in contrast to the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean DMFT in present study was found to be 0.96, a finding similar to the study by Chirca EM et al 13 who reported mean DMFT as 0.7. Studies done by Desai V et al 14 Taboada AO et al 15 and Sadeghi M 16 reported mean DMFT to be 0.12, 1.4 and 1.9 respectively, which is in contrast to the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study carried out in the south of Mexico City [6]. by Olga Taboada-Aranza and Karen Rodríguez-Nieto, the patients had an age range of 6 to 13 years old with a total average of 9 years old, in comparison with the present study, the sex that obtained more dental biofilm was male with a percentage of 53% and females with 47%, in this study, all patients presented accumulation of biofilm on the dental surfaces, the O'Leary index was used and it was determined that the most affected teeth were first permanent molar and upper central incisor.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being preventable through cost-effective actions such as tooth brushing and pit and fissure sealants (together with interproximal cleaning techniques such as flossing, a healthy diet and reduced sugar intake), oral diseases such as dental caries and periodontal diseases continue to be the leading oral health problems in Mexico, affecting a large proportion of the population [1,2,3,4]. Several studies have reported high prevalence and incidence of these problems among the general population, implying significant unmet treatment needs [1,2,3,4]. The dmft index (decayed, missing or filled primary teeth in the primary dentition) ranges from 1.00 to 2.20 and exhibits a prevalence of approximately 60% [5].…”
Section: Introductionmentioning
confidence: 99%